Functional Peculiarities of Lexical Syntagm in Technical Writing - Khamesian, Minoo (Advances in Social Sciences Research Journal, 2017)
Admittedly, in the course of intellectual communication terms tend to be widely used for the expression of concepts and notions of a given branch of knowledge. The meaning or content of words used to express special phenomena or concepts, greatly constituted by the object itself, is a reflection of it in the writer’s mind. The study was an attempt to disclose the functional peculiarities of technical writing on the lexical syntagmatic level of linguistic expressions, focusing on those derivatives, coinages, the creation or the very existence of which would be based on quite definite, well-fixed rules of combining morphemes according to the productive patterns of lexicology, i.e. rules determined by the lexical-morphological categories of the language under investigation, English as the Lingua Franca of science and technology. The analysis showed that in technical writing the presence of such derivatives, besides the need to name new scientific concepts, would have a tendency to acquire metasemiotic overtones. In other words, they might be generally formed by the authors under some contextual circumstances to give the utterance a more stressed effect and enhance the rhetorical impact likely to circulate in the related discourse community.